2018
DOI: 10.1075/tblt.10.10eki
|View full text |Cite
|
Sign up to set email alerts
|

The effects of task type and L2 proficiency on discourse appropriacy in oral task performance

Abstract: Conceived within the TBLT framework, the present study examined pedagogic tasks as vehicles for demonstrating L2 learners' discourse appropriacy in oral production. Eighty ESL learners' discourse appropriacy was measured using three pragmatically-oriented task types (complaint, refusal, and advice) across four different proficiency levels. The findings showed that, for all task types, as general proficiency increased, ratings of discourse appropriacy also increased. We found that there was a pronounced differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Task type was not found to moderate the relationship between FA and the CAF measures. However, in a follow-up study based on the same participants (Ekiert et al, 2018), in which the researchers focused on the complaint, refusal, and advice tasks, their earlier result (no effect of task type) was confirmed for highly proficient learners, but not for less proficient learners, who appeared to struggle especially with the refusal task. Following up on this, Ekiert et al (this issue) found, based on the data of the complaint and refusal tasks performed by a subset of the learners (ten participants from each of the four proficiency levels), that the fewer silent pauses L2 speakers produced between clauses, the more functionally adequate they were perceived.…”
Section: Relationship With Caf Task Type and Language Proficiencymentioning
confidence: 91%
See 2 more Smart Citations
“…Task type was not found to moderate the relationship between FA and the CAF measures. However, in a follow-up study based on the same participants (Ekiert et al, 2018), in which the researchers focused on the complaint, refusal, and advice tasks, their earlier result (no effect of task type) was confirmed for highly proficient learners, but not for less proficient learners, who appeared to struggle especially with the refusal task. Following up on this, Ekiert et al (this issue) found, based on the data of the complaint and refusal tasks performed by a subset of the learners (ten participants from each of the four proficiency levels), that the fewer silent pauses L2 speakers produced between clauses, the more functionally adequate they were perceived.…”
Section: Relationship With Caf Task Type and Language Proficiencymentioning
confidence: 91%
“…FA has been defined in various ways, such as successful information transfer (Upshur & Turner, 1995), pragmatic appropriateness (McNamara & Roever, 2007), text coherence and cohesion (Knoch, 2009), discursive practice and adequacy in oral communication (Ekiert et al, 2018;Révész et al, 2016), and successful task performance (De Jong et al, 2012a;. Considered within the framework of TBLT and TBLA, in line with De Jong et al (2012a; and inspired by the conversational maxims of Grice (1975), we define FA as a task-related construct in terms of successful task completion.…”
Section: Assessment Of Functional Adequacymentioning
confidence: 99%
See 1 more Smart Citation
“…As a typical face-threatening speech act (Brown and Levinson, 1987), refusals have been recognized as a major cross-cultural obstacle (Babai Shishavan and Sharifian, 2016). Ekiert et al (2018) reported that advanced L1 Japanese and Spanish ESL achieved comparable pragmatic appropriacy for refusals, complaints, and advice, but lower proficiency ESL learners with those L1 backgrounds achieved lower pragmatic appropriacy for refusals than for complaints and advice. Our results showed that refusals were harder than suggestions for Chinese EFL learners.…”
Section: Difficulty Of Odcts For Different Speech Actsmentioning
confidence: 98%
“…Thus, drama/theater practice and performance can effectively prepare students to develop the oratory skills required for meaningful communicative activities beyond the classroom setting (3) Cognitive modification: Casteleyn posits that drama and theater productions provide students with opportunities to connect to a real-life audience other than their classmates. Performing drama for an audience beyond the classroom setting is a useful way of fostering students' incentive to practice/perform, and hence to develop a positive mindset for public speaking and performance beyond the classroom setting Casteleyn's (2019) view regarding systematic desensitization and skills training is familiar to many FL or L2 teachers who employ drama in their classrooms, especially those proponents of task-based language teaching (TBLT) (see Ekiert et al, 2018). Note, however, that the third feature proposed by Casteleyn (2019), namely fostering a positive state of mind throughout the involvement of an audience beyond the classroom, has not been sufficiently validated either in the research on drama/theater or that on language education.…”
Section: Literature Reviewmentioning
confidence: 99%